Contribuições das experiências formativas vivenciadas por graduandos durante o curso formação inicial de professores: práticas educativas em espaços não-formais em Bragança-Pará - FREITAS, Renan Ferreira de (2020)
This study aimed to know the knowledge mobilized by the students participating in the course Initial Teacher Training: Educational Practices in non-formal spaces about educational practices experienced in non-formal spaces and playful teaching and learning methodologies. The course aimed to: discuss the Education in Science and Mathematics in the scope of non-formal spaces of teaching and learning; to promote formative experiences in these spaces; to elaborate playful pedagogical material to serve as support in the realization of a trail as the culmination of the course, besides discussions that subsidize the educational praxis to be carried out in these pedagogical spaces and to execute plans of activities to be developed with the student of the Basic Education. Thus, in order to be able to know what students express about non-formal spaces and playful methodologies of teaching and learning, we have used three guiding questions so that they could express what knowledge was mobilized about the theme. There were a total of 16 participants in the course, being students of the courses in Biological Sciences and Natural Sciences, Campus Bragança, Pará. We consider that the course, in a general way, reached its objectives, therefore, the proposed activities were carried out profitably. And even if some students already have knowledge or experienced playful activities in these spaces, many still present a confused understanding on the theme of non-formal spaces and teaching through play activities. With the study we can see, in several passages of the students' speeches, moments in which they highlight the learning provided by the experience. The actions of the course are a way of instigating them to study and research more on the subject, in order to improve their approaches and conceptions when in teaching practice.